Synoptic analysis and satellite monitoring dust phenomenon in Kermanshah province in 1987-2010 (case study: wide spread dust in 17 and 18 June 2009) - kamal omidvar; nesa sepandar (تحقیقات کاربردی علوم جغرافیایی)
In this study, the dust situation in 6 synoptic stations of Kermanshah province was investigated in the period 1987-1992. To study this phenomenon, dust days were extracted in 2009 with code (06) from the current air index. Then data from different bar levels were taken from the National Oceanic and Atmospheric Organization (NCEP / NCAR) database and maps were plotted in the Grads software. Finally, through the processing of MODIS satellite imagery, with the application of the brightness temperature index, round detection and the dust was made and its territory expanded. The results of the study showed that at low ground level, when the European high-pressure system retreated to the north and west, Sudan's low pressure existed in the eastern Mediterranean, and the system moved southwest to the northeast, and when they entered, the disturbance zone is caused due to the lack of moisture in the dust, the main sources of dust in the province of Kermanshah include the deserts of northern Arabia, southern Iraq, and somewhat north of the sub-Saharan Africa.